US Severe Acute Respiratory Syndrome Coronavirus 2 Epsilon Variant: Highly Transmissible but With an Adjusted Muted Host T-Cell Response. (19th April 2022) - Plummer, Jasmine T; Contreras, Deisy; Zhang, Wenjuan; Binek, Aleksandra; Zhang, Ruan; Dezem, Felipe; Chen, Stephanie S; Davis, Brian D; Sincuir Martinez, Jorge; Stotland, Aleksandr; Kreimer, Simion; Makhoul, Elias; et al.
Abstract: Background: The multiple mutations comprising the epsilon variant demonstrate the independent convergent evolution of severe acute respiratory syndrome coronavirus (SARS-CoV-2), with its spike protein mutation L452R present in the delta (L452R), kappa (L452R), and lambda (L452Q) variants. Methods: Coronavirus disease 2019 (COVID-19) variants were detected in 1017 patients using whole-genome sequencing and were assessed for outcome and severity. The mechanistic effects of the epsilon versus non-epsilon variants were investigated using a multiomic approach including cellular response assays and paired cell and host transcriptomic and proteomic profiling. Results: We found that patients carrying the epsilon variant had increased mortality risk but not increased hospitalizations ( P < .02). Cells infected with live epsilon compared with non-epsilon virus displayed increased sensitivity to neutralization antibodies in all patients but a slightly protective response in vaccinated individuals ( P < .001). That the epsilon SARS-CoV-2 variant is more infectious but less virulent is supported mechanistically in the down-regulation of viral processing pathways seen by multiomic analyses. Importantly, this paired transcriptomics and proteomic profiling of host cellular response to live virus revealed an altered leukocyte response and metabolic messenger RNA processing with the epsilon variant. To ascertain host response to SARS-CoV-2 infection, primary COVID-19–positive nasopharyngeal samples were transcriptomically profiled and revealed a differential innate immune response ( P < .001) and an adjusted T-cell response in patients carrying the epsilon variant ( P < .002). In fact, patients infected with SARS-CoV-2 and those vaccinated with the BNT162b2 vaccine have comparable CD4 + /CD8 + T-cell immune responses to the epsilon variant ( P < .05). Conclusions: While the epsilon variant is more infectious, by altering viral processing, we showed that patients with COVID-19 have adapted their innate immune response to this fitter variant. A protective T-cell response molecular signature is generated by this more transmissible variant in both vaccinated and unvaccinated patients. Abstract : Clinical data used to investigate outcome, viral kinetics, T-cell response, cellular, and host transcriptomics/proteomics provided a complete picture of host response during infection with the epsilon severe acute respiratory syndrome coronavirus 2 variant, demonstrating that both humoral and cell-mediated immune responses are crucial for understanding vaccinated and unvaccinated host response to variants.